2015
DOI: 10.1111/1750-3841.13143
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Enterotoxin Production and Cross‐Contamination of Staphylococcus aureus between Food Processing Materials and Ready‐To‐Eat Cooked Fish Paste

Abstract: This study evaluated Staphylococcus aureus growth and subsequent staphylococcal enterotoxin A production in tryptone soy broth and on ready-to-eat cooked fish paste at 12 to 37 °C, as well as cross-contamination between stainless steel, polyethylene, and latex glove at room temperature. A model was developed using Barany and Roberts's growth model, which satisfactorily described the suitable growth of S. aureus with R(2)-adj from 0.94 to 0.99. Except at 12 °C, S. aureus cells in TSB presented a lag time lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…S. aureus is widely distributed in air, water, dust, and the waste of human and animals. Moreover, S. aureus can survive in different foodstuffs over a wide range of temperatures (10–45°C), pHs (4.5–9.3), and NaCl concentrations (up to 15%) (Tango, Hong, Wang, & Oh, ). These characteristics make it easy to facilitate the bacterial contamination of foods during the process of manufacturing, package, storage, and circulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus is widely distributed in air, water, dust, and the waste of human and animals. Moreover, S. aureus can survive in different foodstuffs over a wide range of temperatures (10–45°C), pHs (4.5–9.3), and NaCl concentrations (up to 15%) (Tango, Hong, Wang, & Oh, ). These characteristics make it easy to facilitate the bacterial contamination of foods during the process of manufacturing, package, storage, and circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Some conventional physical treatments have been applied to control and kill bacteria, including thermal inactivation, high pressure, and normal cooking (Shi et al, ). Although bacteria can be killed by these methods, the heat‐resistant enterotoxins can persist, leading to staphylococcal food poisoning, and some physical treatments can cause adverse effects on the food quality (Tango et al, ). In addition to the physical treatments, chemically synthesized preservatives, such as sorbic acid and sorbate, benzoic acid, and benzoate, are also applied in food industry (Calo, Crandall, O'Bryan, & Ricke, ).…”
Section: Introductionmentioning
confidence: 99%
“…The initial time (another expression of TTD) in that study was suggested to be predicted by using the threshold concentration of S. aureus and the established S. aureus growth model in milk. Tango et al ( 2015 ) also analyzed the S. aureus cell density and the time when the toxin could be detected under various temperatures in cooked fish paste. However, both of them didn't apply and validate this method in their article.…”
Section: Discussionmentioning
confidence: 99%
“…(Reij et al, 2004;Jelena et al, 2011). Previously several studies showed that some thermostable enterotoxin of Staphylococcus aureus and Escherichia coli would not destroy completely even after cooking of seafood or if the food cooked properly, due to improper handling recontamination can take place and consumption of this type of food causes severe food poisoning (Ayulo et al, 1994;Vieira et al, 2001;Omeo et al, 2005;Simon and Sanjeev, 2007;Beleneva, 2011;Tango et al, 2015). On the other hand, cooked-frozen fish are widely consumed by working people in their busy life.…”
Section: Introductionmentioning
confidence: 99%